Factors Affecting Employee Turnover Intention in Commercial Banks of Butwal Sub-Metropolitan City, Nepal - Ghimire, Albina; Prasad Chaudhary, Bhagawati (Kalika Journal of Multidisciplinary Research, 2025)
This research aims to examine the different connections between essential organizational factors: Employer Support, Job Satisfaction, Role Changes, Cultural Clash, and Work-Life Balance, and their impact on Employee Turnover Intention within commercial banks. The study intends to evaluate the strength and direction of these relationships to gain insights into the various underlying reasons for turnover intention. The study adopted a descriptive and explanatory design, with 258 employees of commercial banks located in Butwal Sub-Metropolitan City, Nepal, selected through purposive sampling, where the employees had to have at least one year of work experience in banks. The measurement model was confirmed for its validity and reliability through the evaluation of composite reliability, convergent validity, discriminant validity, and the application of bootstrapping techniques for hypothesis testing. The results indicate that Work-Life Balance and Job Satisfaction are the leading predictors of turnover intention among banking personnel, while Employer Support, Role Changes, and Cultural Clash have a relatively weaker influence. The results are of considerable importance to HR managers and policymakers. Emphasizing the well-being and job satisfaction of employees ought to be regarded as a strategic method for minimizing turnover and promoting organizational stability. Additionally, the suggested framework presents opportunities for wider implementation across various service sectors, thus improving its generalizability and practical significance.